2020
DOI: 10.21037/jgo-20-245
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy for patients with locally advanced or unresectable extra-hepatic biliary cancer

Abstract: Background: Although surgical resection is the preferred curative-intent treatment option for patients with non-metastatic, extra-hepatic biliary cancer (EBC), radiotherapy (RT) or chemoradiotherapy (CRT) may be utilized in select cases when surgical resection is not feasible. The purpose of this study is to report the efficacy and adverse events (AEs) associated with CRT for patients with locally advanced and unresectable EBC. Methods: This was a retrospective cohort study of patients with EBC, including extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It would be reasonable to conclude that dCRT with traditional radiotherapy dose techniques and fluorouracilbased chemosensitization is not truly curative but instead only palliative. However, studies have demonstrated more promising outcomes when radiation dose escalation can be achieved safely (25).…”
Section: Discussionmentioning
confidence: 99%
“…It would be reasonable to conclude that dCRT with traditional radiotherapy dose techniques and fluorouracilbased chemosensitization is not truly curative but instead only palliative. However, studies have demonstrated more promising outcomes when radiation dose escalation can be achieved safely (25).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative regimen, particularly before OLT, is 40.5 to 45 Gy in 1.5 Gy twice-daily fractions, followed by ILBT to a dose of 9.3 Gy with HDR brachytherapy or 20 Gy delivered over 20 to 25 hours with low dose rate brachytherapy, each prescribed to 1 cm depth 51,52,54,55. For definitive RT, doses of 45 to 60 Gy in 1.8 to 2.0 Gy fractions have most commonly been used 101–103,122,120. Hypofractionated regimens of 45 to 67.5 Gy in 15 fractions and 66 to 72 Gy in 10 to 22 fractions have also been used 104,106.…”
Section: Methodsmentioning
confidence: 99%
“…100,101 A single institution retrospective cohort study of 48 patients with unresectable EHCC treated with CRT found the 2-, 3-, and 5-year OS rates to 33% (95% CI: 22%-50%), 20% (95% CI: 11% to 36%), and 7% (95% CI: 2% to 20%), respectively, with a median OS of 12 months. 102 On univariate analysis, biologically effective dose (BED) > 59.5 Gy10 was associated with improved OS (HR = 0.40; 95% CI = 0.18-0.92; P = 0.03) and PFS (HR = 0.37; 95% CI = 0.16-0.84; P = 0.02), and on multivariate analysis it remained associated with PFS (HR = 0.34; 95% CI = 0.15-0.78; P = 0.01), suggesting a benefit to dose escalation for this disease. However, another retrospective series of 80 patients with unresectable EHCC failed to show a benefit to dose escalation.…”
Section: Unresectable Ehccmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis of 48 patients with gallbladder carcinoma and cholangiocarcinoma treated between 1998 and 2018 and a median radiotherapy dose of 50.4 Gy, achieved a median OS of 12.0 mo with OS at 2, 3, and 5 years of 33%, 20%, and 7%, respectively. In the univariate analysis, biologically effective dose (BED) > 59.5 Gy 10 was associated with improved PFS and OS and primary tumor size was associated with worsening PFS[ 44 ].…”
Section: Radiotherapymentioning
confidence: 99%